Distribution of the Ponto-Caspian Amphipods in Turkish Fresh Waters: An Overview - OZBEK, M. (Mediterranean Marine Science, 2011)
To date, 13 amphipod species [Dikerogammarus haemobaphes(Eichwald, 1841); D. istanbulensis Özbek & Özkan, 2011; D. gruberi Mateus & Mateus, 1990; Echinogammarus ischnusStebbing, 1899; Pontogammarus robustoides (Sars, 1894); P. maeoticus(Sowinsky, 1894); P. aestuarius(Derzhavin, 1924); Obesogammarus turcarum Stock, 1974; Amathillina cristata Sars, 1894; Chelicorophium curvispinum Sars, 1895; C. maeoticum(Sowinsky, 1898); C. robustum Sars, 1895 and Orchestia cavimana Heller, 1865] were reported from Turkey as the representatives of Ponto-Caspian amphipod fauna. Previous records and current distributional patterns of Ponto-Caspian amphipod crustaceans in Turkish inland waters were investigated. Three new localities were revealed as one of the southernmost points in distributional area of Pontogammarus robustoides (Sars, 1894).